Períodos de interferência de Mucuna aterrima (Piper & Tracy) em cana-de-açúcar e seu controle químico - Bressanin, Fernanda Nunes [UNESP] (2014)
The sugar cane extracts large amounts of nutrients from the soil and to partially restore fertility, producers have the option of using green manure during the reform of the sugar plantation. The velvet bean (Mucuna aterrima), one of the most suitable species as green manure, if not handled properly can become a weed and thus interfere directly and indirectly in the culture. One of the factors that will determine the level of interference is the period of coexistence between culture and weeds. Three stand out: the critical duration of weed competition (PAI), critical weed free period (PTPI) and the critical period for weed competition (PCPI). Thus, we determined the periods of interference velvet bean in cane sugar and, knowing the periods, study which herbicides and application methods are effective for their control. Was 18 treatments divided into 2 groups. In the first, of , 0-30 days, 0-45 days, 0-60 days, 0-90 days, 0-120 days e 0-150 days, 0-180 days, 0-harvest. In the second group, of 10o to 18o treatments, preceded to the opposite of the previous group in relation to weed control, in other words, culture remained living with the weed community from budding to the same periods described above. The experiments were arranged in a randomized block design, with each treatment in for repetitions. The results were subjected to regression analysis, and interference periods determined considering 5% loss in production. For the control experiment velvet bean in the pre-emergence herbicides were used amicarbazone (1175 g ha-1); tebuthiuron (900 g ha-1) and sulfentrazone (600 g ha-1) and for the experiments applied post-emergence herbicides than the three earlier, were used, 2,4-D amine (670 g ha-1); atrazine (3250 g ha-1); Carfentrazone-ethyl (35 g i.a. ha-1) and mesotrione (133 g ha-1) alone applied post-emergence to plants at three different developmental stages: Experiment 1: Two unfolded sheets (BBCH - 12); Experiment 2: Seven ...